Modelling root and stem lodging in sunflower - Sposaro, M.M. (2010)
Stem and root lodging constitute significant adversities to sunflower (Helianthus annuus L.) cropping in Argentina. We have adapted previously developed models of the lodging process in cereals to the particularities of sunflower by using functions, developed using data obtained by mechanical lodging, for the [root failure moment/plant anchorage] and [stem failure moment/thickness of stem wall] relationships, and estimates of plant area loaded by wind gusts. The model uses this information to estimate wind failure speed (i.e., the wind speed at which lodging [stem or root, as appropriate] is expected to occur). The model was tested against information (plant and soil characteristics, measured wind gust velocity immediately preceding rainfall) obtained in 26 naturally lodged plots (6 stem-lodged, 20 root-lodged) which occurred across a network of trials (2 seasons, 4 sites, 3 hybrids, 4 crop population densities, all experiments fitted with automatic meteorological stations). Lodging events took place over a range of crop developmental stages between visible capitulum and harvest maturity. Lodging index (proportion of plants lodged) against the difference between observed and model-estimated wind failure speeds showed that the model had good predictive skill across the range of conditions explored in these experiments and was able to distinguish between hybrids of differential susceptibility to lodging within the same experiment. Sensitivity analyses showed that the principal determinants of lodging susceptibility were root plate diameter, stem wall thickness, and the area of the plant loaded by wind gusts. Within the observed ranges (almost twofold) of stem height and stem natural frequency, these two variables had little influence on lodging susceptibility. We conclude that the model, despite the simplifications incorporated into its structure, provides an effective and useful tool for the integration of the complex factors that determine lodging susceptibility in this species.